Food Security, Safety, and Sustainability—Getting the Trade-Offs Right - Vågsholm, Ivar; Arzoomand, Naser Shah; Boqvist, Sofia (Frontiers in Sustainable Food Systems, 2020)
The United Nations sustainable development goals include eradication of hunger. To feed 10 billion persons 2050, we need to get the trade-offs right between sustainability, food security, food safety and make better use of food already produced. The hierarchy of strategies for reducing food losses and waste are in descending order source reduction, reusing or reprocessing surplus foods, recycle food as feed for animals, recover the energy as biofuels, nutrients as compost, or raw materials for industry, while as last resorts one may consider recovering the energy by incineration or dumping as garbage in landfills. This paper will explore the trade-offs inherent when aiming at triple goals of sustainability, food security and safety looking at these strategies for reducing food losses and waste and resource footprints. Intensification of food production and circular food systems could be parts of these solutions to future food security. In this regard could our future trade-offs be informed by the experiences from the use of antimicrobials to intensify food production and from the outbreak of bovine spongiform encephalopathy (BSE) in terms of circular food production? There is no trade-off between intensification of food production aided by antimicrobials and the public health risks from antimicrobial resistance due to the zoo-technical use of antimicrobials. A sustainable future requires control of antimicrobial resistance. If one avoids that cycles of nutrients become cycles of pathogens and/or hazards, circular food production systems will a major contribution to the future sustainable food security. Source reduction i.e., limiting food losses and waste appears to the strategy most promising for achieving sustainability. By using artificial intelligence and intelligent packaging major progress is possible, with the added benefit of better control of food fraud. A changed diet - eating more plant-based foods and not eating animal protein produced by edible feedstuffs, and source reduction of the food lost or wasted should enable us to feed at least an additional billion persons. Solutions to sustainability and food security should integrate food safety considerations from the start.